2017
DOI: 10.18632/oncotarget.22825
|View full text |Cite
|
Sign up to set email alerts
|

Genomic alterations of ERBB receptors in cancer: clinical implications

Abstract: The ERBB family of receptor tyrosine kinases has been implicated in carcinogenesis for over three decades with rigorous attention to EGFR and HER2. ERBB receptors, consisting of EGFR, HER2, HER3, and HER4 are part of a complicated signaling network that activates downstream signaling pathways including PI3K/AKT, Ras/Raf/MAPK, JAK/STAT and PKC. It is well established that EGFR is amplified and/or mutated in gliomas and non-small-cell lung carcinoma while HER2 is amplified and/or over-expressed in breast, gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 148 publications
3
98
0
1
Order By: Relevance
“…For example, EGFR family receptors are amplified and/or mutated in various human tumors, including gliomas, non-small-cell lung carcinoma, breast, gastric, and ovarian cancers. [205][206][207] Activation of EGFR results in the recruitment of Grb2, a SH2 domain protein complexed with the guanine exchange factor son-of-sevenless (Sos), to the tyrosine-phosphorylated EGFR. [205][206][207] Activation of EGFR results in the recruitment of Grb2, a SH2 domain protein complexed with the guanine exchange factor son-of-sevenless (Sos), to the tyrosine-phosphorylated EGFR.…”
Section: Rtks Cancer Cells and Primary Ciliamentioning
confidence: 99%
“…For example, EGFR family receptors are amplified and/or mutated in various human tumors, including gliomas, non-small-cell lung carcinoma, breast, gastric, and ovarian cancers. [205][206][207] Activation of EGFR results in the recruitment of Grb2, a SH2 domain protein complexed with the guanine exchange factor son-of-sevenless (Sos), to the tyrosine-phosphorylated EGFR. [205][206][207] Activation of EGFR results in the recruitment of Grb2, a SH2 domain protein complexed with the guanine exchange factor son-of-sevenless (Sos), to the tyrosine-phosphorylated EGFR.…”
Section: Rtks Cancer Cells and Primary Ciliamentioning
confidence: 99%
“…HER2/neu gene amplification and/or protein overexpression are found in many human cancers, such as breast, bladder, and gastric cancer. Five HER2 inhibitors are currently FDA-approved to treat HER2-amplified/overexpressing breast cancers 48. In 2008 Karam et al reviewed the data available on VPD, after describing success treating a recurrent, symptomatic case with trastuzumab.…”
Section: Resultsmentioning
confidence: 99%
“…A report suggests that ERBB2 and ERBB3 are down-regulated by DNA-damaging agent such as cisplatin via ERK and p38 signaling pathway [26]. It is also demonstrated that ERBB3 is involved in resistance to EGFR or ERBB2 targeted therapy for cancer [27]. Furthermore, the study of nanoparticles targeting ERBB2 and microRNA21 suggests the importance of ERBB signaling in cancer [28].…”
Section: Discussionmentioning
confidence: 99%